2019
DOI: 10.1002/cpt.1506
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography Imaging of [11C]Rosuvastatin Hepatic Concentrations and Hepatobiliary Transport in Humans in the Absence and Presence of Cyclosporin A

Abstract: Using positron emission tomography imaging, we determined the hepatic concentrations and hepatobiliary transport of [11C]rosuvastatin (RSV; i.v. injection) in the absence (n = 6) and presence (n = 4 of 6) of cyclosporin A (CsA; i.v. infusion) following a therapeutic dose of unlabeled RSV (5 mg, p.o.) in healthy human volunteers. The sinusoidal uptake, sinusoidal efflux, and biliary efflux clearance (CL; mL/minute) of [11C]RSV, estimated through compartment modeling were 1,205.6 ± 384.8, 16.2 ± 11.2, and 5.1 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 52 publications
4
62
2
Order By: Relevance
“…Generally, human PK profiles and DDIs are discussed based on drug concentration in plasma and/or urine, because blood and urine collection are easy and less invasive procedures. However, PET imaging technology by which tissue accumulation of radiolabeled transporter substrates is detectable could fill the current gap for accurate DDI prediction in tissues and help identification of rate‐determining process in the elimination . Ørntoft et al demonstrated that the use of bile acid tracer [ 11 C]‐cholylsarcosine as an example for an imaging marker provided a proof‐of‐concept for the feasibility of visualizing transporter functions involved in bile formation in humans.…”
Section: Recommendationsmentioning
confidence: 99%
“…Generally, human PK profiles and DDIs are discussed based on drug concentration in plasma and/or urine, because blood and urine collection are easy and less invasive procedures. However, PET imaging technology by which tissue accumulation of radiolabeled transporter substrates is detectable could fill the current gap for accurate DDI prediction in tissues and help identification of rate‐determining process in the elimination . Ørntoft et al demonstrated that the use of bile acid tracer [ 11 C]‐cholylsarcosine as an example for an imaging marker provided a proof‐of‐concept for the feasibility of visualizing transporter functions involved in bile formation in humans.…”
Section: Recommendationsmentioning
confidence: 99%
“…In one study with the radiolabeled statin drug [ 11 C]rosuvastatin in rats, the presence of rifampicin caused a pronounced increase in the blood AUC as well as a reduction in the liver uptake clearance of [ 11 C] rosuvastatin, which was attributed to an inhibition of OATP uptake transporters in rats [94]. Additionally, in one study in healthy human volunteers, intravenous infusion of cyclosporine A caused an increase in the [ 11 C]rosuvastatin blood AUC and also inhibited the liver uptake clearance in three out of four subjects [37]. These results supported an involvement of OATP transporters in the uptake of [ 11 C]rosuvastatin from the blood into the liver in humans.…”
Section: Pet To Assess Transporter-mediated Ddismentioning
confidence: 99%
“…In combination with appropriate radiolabeled probe substrates which are transported by one or several hepatic transporters, PET and SPECT have a great potential to assess the activity of hepatic transporters in vivo in humans under various conditions [33]. Moreover, in combination with radiolabeled drugs or drug candidates, these imaging methods can be potentially used to mechanistically assess transporter-mediated DDIs [35] and to validate in vitro-in vivo extrapolation (IVIVE) methods of hepatic drug clearance [36,37]. Another imaging method, which is of considerable clinical interest, is magnetic resonance imaging (MRI) in combination with contrast agents which enter and leave hepatocytes mediated by hepatic transporters [33].…”
Section: Article Highlightsmentioning
confidence: 99%
See 2 more Smart Citations